Suppression of Tumor and Metastasis Progression through the Scaffolding Functions of SSeCKS/Gravin/AKAP12 - Gelman, Irwin H. (2012)
Scaffolding proteins such as SSeCKS/Gravin/AKAP12 (“AKAP12”) are thought to control oncogenic signaling pathways by regulating key mediators in a spatiotemporal manner. The downregulation of AKAP12 in many human cancers, often associated with promoter hypermethylation, or the loss of its locus at 6q24-25.2, correlates with progression to malignancy and metastasis. The forced re-expression of AKAP12 in cancer cell lines suppresses in vitro parameters of oncogenic growth, invasiveness and cell motility through its ability to scaffold protein kinase C (PKC), F-actin, cyclins, Src and phosphoinositides, and possibly through additional scaffolding domains for PKA, calmodulin, β1,4-galactosyltransferase-polypeptide-1, β2-adrenergic receptors and cAMP-specific 3′,5′-cyclic phosphodiesterase 4D. Moreover, AKAP12 re-expression in tumor models results in metastasis suppression through the inhibition of Src-regulated, VEGF-mediated neovascularization at distal sites. The current review will describe the emerging understanding of how AKAP12 regulates cellular senescence and oncogenic progression at the level of tumor cells and tumor-associated microenvironment via its multiple scaffolding functions.